2022
DOI: 10.2147/jir.s374318
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Activation of the cGAS-STING Pathway is Regulated by Mitochondrial Dysfunction and Mitochondrial DNA Leakage in Endometritis

Abstract: Introduction: Chronic endometritis is a common disease in women of childbearing age and can cause pelvic inflammatory disease. The cGAS-STING pathway plays an important role in many inflammatory diseases. Purpose: The aim of this study was to investigate the relationship between the cGAS-STING pathway and endometritis. Methods: We collected endometrium samples from patients with endometritis to detect changes in the cGAS-STING pathway. In vitro, human endometrial stromal cells (HESC) were stimulated with lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Antioxidant enzymes, including SOD, SOD2, and peroxidases such as GPX and CAT, play a crucial role in antioxidant defense by regulating ROS levels [ 33 , 34 ]. A high concentration of LPS leads to abnormal ROS and MMP levels; promotes the production of inflammatory factors such as TNF-α, IL-1β, IL-6, and IL-8, causing oxidative damage and mitochondrial dysfunction [ 2 , 35 ]; and even leads to apoptosis [ 36 , 37 ]. Cecropin A has been shown to inhibit the production of TNF-α and IL-1β induced by LPS in mouse macrophage-derived RAW264.7 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant enzymes, including SOD, SOD2, and peroxidases such as GPX and CAT, play a crucial role in antioxidant defense by regulating ROS levels [ 33 , 34 ]. A high concentration of LPS leads to abnormal ROS and MMP levels; promotes the production of inflammatory factors such as TNF-α, IL-1β, IL-6, and IL-8, causing oxidative damage and mitochondrial dysfunction [ 2 , 35 ]; and even leads to apoptosis [ 36 , 37 ]. Cecropin A has been shown to inhibit the production of TNF-α and IL-1β induced by LPS in mouse macrophage-derived RAW264.7 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term feeding of dairy cows with a high-concentrate diet poses a significant risk of sub-acute ruminal acidosis (SARA), leading to a high concentration of lipopolysaccharides (LPSs) in the circulatory system and triggering a systemic inflammatory response [ 1 ]. A previous study demonstrated that elevated LPS levels correlate with increased reactive oxygen species (ROS) and reduced mitochondrial membrane potential, ultimately causing mitochondrial dysfunction [ 2 ]. Furthermore, LPS leads to the upregulation of NADPH Oxidase (NOX), then resulting in an increase in ROS levels, which is a marker of oxidative stress [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…cGAS recognizes the mtDNA and produces cGAMP, which inhibits the proliferation of endothelial cells through the downregulation of the YAP1 signaling pathway. Another study found that LPS induced mitochondrial dysfunction in endometrial mesenchymal cells through activation of the cGAS-STING pathway, induced mtDNA leakage, and promoted endometritis [ 83 ]. In addition, Interleukin-1β [ 84 ], palmitic acid (PA)-induced Lipotoxicity [ 85 ], TNF [ 86 ], and Electronic Cigarettes [ 87 ] are all involved in a variety of physiological and pathological processes through the activation of innate immune signaling pathways by mtDNA.…”
Section: Other Agentsmentioning
confidence: 99%
“…In another study using human endometrial stromal cells (HESCs) stimulated with lipopolysaccharide (LPS), cytoplasmic dsDNA, the cGAS-STING pathway, and IFN-β1 , IL-1β , IL-6 , and IL-8 gene expression were increased after LPS stimulation. Furthermore, when mtDNA was isolated and extracted from HESCs and then transfected into HESCs, the levels of cGAS-STING pathway proteins increased ( 142 ). Similarly, in a study investigating the role of the pro-inflammatory cytokine interleukin-6 (IL-6) on human endometrial adenocarcinoma MFE-296 cells, IL-6 increased the generation of ROS by enhancing NADH oxidase levels and inducing the cellular release of mtDNA.…”
Section: Can Mtdna Serve As An Ec Biomarker?mentioning
confidence: 99%